2021
DOI: 10.1177/14604582211033014
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data-based adverse drug reactions detection from the Korea Adverse Event Reporting System databases with electronic health records-based detection algorithm

Abstract: Pharmacovigilance involves monitoring of drugs and their adverse drug reactions (ADRs) and is essential for their safety post-marketing. Because of the different types and structures of medical databases, several previous surveillance studies have analyzed only one database. In the present study, we extracted potential drug–ADR pairs from electronic health record (EHR) data using the MetaNurse algorithm and analyzed them using the Korean Adverse Event Reporting System (KAERS) database for systematic validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Voluntary reporting (physician self-reporting) forms a small portion of ADR information. [ 15 ]. This identifies the lowest number of errors compared to others.…”
Section: Reviewmentioning
confidence: 99%
“…Voluntary reporting (physician self-reporting) forms a small portion of ADR information. [ 15 ]. This identifies the lowest number of errors compared to others.…”
Section: Reviewmentioning
confidence: 99%
“…Spontaneous adverse event reports are another real-world data specialized for adverse events. The Korea Institute of Drug Safety & Risk Management (Ministry of Food and Drug Safety) provides Korea Adverse Event Reporting System (KAERS) database (KIDS-KD) for pharmacovigilance analysis (Shin et al 2021). Several studies have shown that signals of adverse events were detected by data mining on KIDS-KD.…”
Section: Introductionmentioning
confidence: 99%